Opposing the toxic apartheid: The painted veil of the COVID‐19 pandemic, race and racism - Gao, Grace; Sai, Linna (Gender, work, and organization, 2021)
This article is a personal reflection of how the coronavirus exposes ‘shocking’ levels of racism against us, and our vulnerability as Chinese women living in Britain. By reflecting our experiences of verbal and physical race‐based violence connected to coronavirus, we explore the fluidity of our racial identities, the taken‐for‐granted racial stereotypes and white privilege, and everyday racism in the UK. Can the vulnerable use vulnerability as an agent to shift the moment of helplessness? We contribute to the uncomfortable yet important debate on racism against Chinese women living in the UK through voicing up our embodied vulnerability as invisible and disempowered subjects to this viral anti‐Chinese racism. This is a form of resistance where we care for the racialized and marginalized others. In doing so, we lift the painted veil of the pandemic, race and racism to collectively combat racial inequalities.